2017
DOI: 10.1093/scan/nsx054
|View full text |Cite
|
Sign up to set email alerts
|

Humor drawings evoked temporal and spectral EEG processes

Abstract: The study aimed to explore the humor processing elicited through the manipulation of artistic drawings. Using the Comprehension–Elaboration Theory of humor as the main research background, the experiment manipulated the head portraits of celebrities based on the independent variables of facial deformation (large/small) and addition of affective features (positive/negative). A 64-channel electroencephalography was recorded in 30 participants while viewing the incongruous drawings of celebrities. The electroence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 130 publications
(154 reference statements)
0
7
0
Order By: Relevance
“…Therefore, the N600 component was selected and the time window was averaged at this interval (yellow area) after target onset. This section was based on recommendations made in previous N600 research [ 17 , 19 , 22 ]. However, there is no obvious 400 waveform over the 300–500 ms time period after stimulus onset.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the N600 component was selected and the time window was averaged at this interval (yellow area) after target onset. This section was based on recommendations made in previous N600 research [ 17 , 19 , 22 ]. However, there is no obvious 400 waveform over the 300–500 ms time period after stimulus onset.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have shown that the N600 is triggered by practical experience and logical thinking or comprehension of the rules as well as inconsistent stimuli such as those provided by humor and entertainment [15,17]. Therefore, the N600 is often triggered in the detection of humor or jokes, mainly in the observation of N270, N400, N600-800, and even 1500 ms slow waves [14,[17][18][19].…”
Section: N600mentioning
confidence: 99%
See 1 more Smart Citation
“…One single study focused on verbal materials and observed a power decrease in the beta range of the EEG [88]. When processing visual stimuli, the involvement of several frequency ranges [91] or a specific role for alpha oscillations and creative cognition in humor [92] was found.…”
Section: Eeg Indexes For Mind Reading Pragmaticsmentioning
confidence: 99%
“…Many other neuroscientific studies in relevant art fields have revealed that the cognitive conflict and memories inspired by surreal images produce relatively stronger theta activity in the center of the frontal lobe ( Ruzzoli et al, 2020 ). Humorous drawings elicit theta activity in the parietal lobe and posterior cingulate cortex ( Wang et al, 2017 ). Compared with non-award-winning advertisements, it has been found that award-winning advertisements that combine artistic aesthetics with marketing elicit greater theta and alpha activity in the right frontotemporal regions ( Wang et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%